Ecological Risk and Adsorption of Toxic Metals from Gbalahi Landfill Leachate using Chicken Eggshells as a Low Cost Adsorbent - Kan-Uge, J; Alhassan, E.H; Duwiejuah, A.B; Iddrisu, F.T; Gameli, B.H.R (West African journal of applied ecology, 2023)
Pollution is a world-wide talked about subject but little has been achieved in the 21 (st) century in terms of improvement of aquatic environment, water quality and reducing human health risks. One of the most effective methods of removing toxic metals is adsorption. The study was to assess the ecological risk and efficacy of chicken eggshell as a low cost adsorbent for the removal of toxic metals from Gbalahi landfill leachate. Chicken eggshells (1 g, 2 g, 4 g, 6 g and 8 g) were added to 100 mg [L.sup.-1] each of the spiked ternary leachate (1 mg [L.sup.-1], 5 mg [L.sup.-1], 10 mg [L.sup.-1], 25 mg [L.sup.-1] and 50 mg [L.sup.-1]) and agitated for 60 minutes at a constant temperature (25 [degrees]C). The leachates, and elutes were obtained and transported to the Ecological Laboratory of University of Ghana for initial analysis. The study revealed that 0.2060 mg [L.sup.-1] for cadmium (Cd), 0.0060 mg [L.sup.-1] for chromium (Cr), 0.0010 mg [L.sup.-1] for lead (Pb), 0.0012 mg [L.sup.-1] for mercury (Hg), 0.0024 mg [L.sup.-1] for arsenic (As) and 0.3410 mg [L.sup.-1] for nickel (Ni) were present in the leachate. The removal efficiencies for Cd, Hg, and Pb ranged from 98.67% to 99.99%, 99.89% to 99.99%, and 99.98% to 99.99%, respectively. Langmuir model (0.46 [less than or equal to] [R.sup.2] [less than or equal to] 0.84) showed a better fit for the adsorption of the toxic metals by chicken eggshells than Freundlich model (0.26 [less than or equal to] [R.sup.2] [less than or equal to] 0.40). Cadmium and nickel proved to be the metals with the highest level of toxicity. Chicken eggshells have a high adsorption efficiency in the landfill leachate. The pH of the leachates were favourable for the adsorption. The toxic metals in the leachate were within the low contamination and low-risk category indicating low ecological risks. Low-cost chicken eggshells can be used as an economically efficient material for the removal of cadmium, mercury and lead from landfill leachate. More adsorptive studies should be carried out using chicken eggshells as an adsorbent to remediate other wastewater in order to gain a broad knowledge on the adsorbent's applicability.